Comparative evaluation of the antiplaque effectiveness of green tea catechin mouthwash with chlorhexidine gluconate - Kaur, Harjit (Medknow Publications & Media Pvt Ltd, 2014)
AIM: The aim of this study is to compare the antiplaque efficacy of green tea catechin mouthwash with chlorhexidine gluconate mouthwash. MATERIALS AND METHODS: A single blinded cross-over study was conducted among 30 participants in the age group of 18-25 years. The mouthwash samples for the study were previously labeled assigning the letters: A (0.25% of green tea catechin mouthwash) and B (0.12% of chlorhexidine mouthwash). The study subjects were randomly divided into two groups of 15 each and the study was divided into two phases. In phase I, the mouthwash A was given to one group and other group was given mouthwash B. After a 15 day washout period, in phase II, both groups were given other mouthwash. At the end of each phase of 1 week, plaque score was recorded by using Turesky modification of the Quigley-Hein plaque index. RESULTS: The plaque scores were compared and the difference between the green tea catechin and chlorhexidine mouthwash was determined by t-test. The difference between plaque scores were not statistically significant (P > 0.05). The results showed that both the groups that is green tea catechin mouthwash (0.25%) and chlorhexidine mouthwash (0.12%) have comparable results in plaque reduction. CONCLUSION: This study supports the effectiveness of green tea catechin mouthwash as an antiplaque agent. It should be explored as a cost-effective, long-term antiplaque rinse with prophylactic benefits.